Vintage Luxury Fashion Exploring the Rise of the Secondhand Clothing Trade (Palgrave Advances in Luxury,, 2018)
Providing a critical insight into the growth of the second-hand luxury and vintage fashion industry, this book offers a compendium of business developments from across the globe, including examples from Europe, the Middle East and Asia. The 'pre-loved or pre-owned' clothing trade has grown as an economic entity, providing a living for over 100,000 people and creating a desirable and essential clothing source in under-developed economies. By debating and deliberating contemporary cases, the authors illustrate how companies can optimise key managerial activities surrounding product branding, location marketing and supply chain buying. This timely collection is an important read for anyone involved in fashion, but particularly those interested in the retail and marketing perspective of the industry, as it explores an emerging and significant retail format.